How parboiling and drying affect the colour and functional characteristics of yam (Dioscorea cayenensis-rotundata) flours - AKISSOE, H. NOËL; HOUNHOUIGAN, DJIDJOHO JOSEPH; Mestres, Christian; Nago, GUY FORTUNÉ (My University, 2003)
Colour and texture are important features of amala, a traditional thick paste obtained from dry yam flour. Tubers from eight yam cultivars were blanched at 65 °C for 20 min and dried at 40 °C for 5 days to test biochemical, thermal and pasting changes occurring during traditional yam flour processing. Blanching reduced peroxidase activity and drying reduced polyphenoloxidase activity, but total phenol content and the brown index of flour and of amala increased dramatically during the latter operations. The brown index of amala was significantly correlated with the total phenol content of the flour (r=0.84) and the peroxidase activity of the fresh tubers (r=0.75). Amylose content and starch gelatinization enthalpy remained stable. For all cultivars, drying significantly increased the onset gelatinization temperature, suggesting the occurrence of starch annealing. The latter leads to a reduction in swelling power and solubility during pasting, and hence to a lower paste viscosity.
Keywords: Yam; Phenols; Polyphenoloxidase; Peroxidase; Blanching; Viscosity